What Motivates Social Media Users to Share Fake News, and What are its Impacts? A Systematic Literature Review - Azahah Abu Hassan Shaari; Muhammad Rahim Kamaluddin; Zainal Abidin; Muhammad Adnan Pitchan; Shalini Munusamy (Changing Societies & Personalities)
The use of fake news to deceive the public, manipulate opinions, and advance various agendas has posed significant challenges in its dissemination online. This study systematically examines the motivations for and effects of online fake news dissemination based on English-language articles published in international peer-reviewed journals between 2018 and 2023. These articles were identified through a systematic search of the Scopus and Web of Science databases, conducted between July 1, 2023, and to January 31, 2024, following PRISMA guidelines. Twenty-one studies met the eligibility criteria, their methodologies included quantitative, qualitative, systematic literature reviews, and mixed methods. Thematic analysis revealed four key factors contributing to fake news dissemination: (a) psychological drives, such as the need for validation and sensation-seeking; (b) technological influences, including bots and clickbait; (c) political motives, particularly during elections; and (d) the role of media literacy in mitigating or exacerbating misinformation spread. The effects of fake news dissemination were categorized into public health concerns, socioeconomic consequences, and conflict. This review helps explain the dynamics of fake news dissemination within five years, aiding individuals and organizations in understanding the online misinformation spreads online. These insights will help stakeholders with knowledge to count fake news and reduce its societal harm.